Reduction of the vertical vestibular-ocular reflex in military aircraft pilots exposed to tactical, high-performance flight - Bertolini, Giovanni; Pagnamenta, Alberto; Kunz, Andres; Del Torso, Aleardo; Bron, Denis (Frontiers in Neurology, 2023)
Background: Exposure to high-performance flight stresses the vestibular system and may lead to adaptive changes in the vestibular responses of pilots. We investigated the vestibular-ocular reflex of pilots with different histories of flight exposure both with respect to hours of flight and flight conditions (tactical, high-performance vs non-high-performance) to evaluate the if and how adaptative changes are observable. Methods: We evaluated the vestibular ocular reflex of aircraft pilots using the video Head Impulse Test. In study 1, we assessed three groups of military pilots: Group 1 - 68 pilots with few hours of flight experience (<300h) in non-high-performance flight condition; Group 2 – 15 pilots with many hours of flight (>3000h) and regularly flying tactical, high-performance flight conditions; Group 3 – 8 pilots with many hours of flight (>3000h) but not exposed to tactical, high-performance flight conditions. In study 2 four trainee pilots were followed up and tested 3 times over a 4-year period: 1) <300 h of flight on civil aircraft; 2) shortly after exposure to aerobatic training and with <2000 h of overall flight); 3) after training on tactical, high-performance aircrafts (F/A 18) and more than 2000h of flight. Results: Study 1: Pilots of tactical, high-performance aircrafts (Group 2) had significantly lower gain values (p<0.05) as compared to Group 1 and 3, selectively for the vertical semicircular canals. They also had a statistically (p=0.022) higher proportion (0.53) of pathological values in at least one vertical semicircular canal as compared to the other groups. Study 2: A statistically significant (p<0.05) decrease in the rVOR gains of all vertical semicircular canals, but not of the horizontal canals, was observed. Two pilots had a pathological value in at least one vertical semicircular canal in the third test. Discussion: The results evidence a decrease of the gain of the vestibular-ocular reflex as measured with the video head impulse test for the vertical canals. This decrease appears to be associated with the exposure to tactical, high-performance flight rather than with the overall flight experience.